(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
Artificial intelligence (AI) is one of the most innovative and promising technologies, with applications ranging from healthcare to education and social services. In the field of disability, new AI-based technologies offer numerous benefits, such as greater autonomy, motor rehabilitation and new opportunities for accessibility and inclusion. Although there are ethical and social challenges, the application of AI in disability is one of the most promising areas for an inclusive society. Finally, the importance of an interdisciplinary and inclusive approach is emphasised as necessary to ensure equity and sustainability in the development of these technologies.